Simultaneous assessement of social skills and behavior problems: Education and gender - Alessandra Turini BOLSONI-SILVA; Sonia Regina LOUREIRO (Estudos de Psicologia (Campinas))
Abstract The aim was to compare the social skills of preschool and school-age children, considering groups differentiated by behavior problem indicators, according to the assessment performed by parents and teachers. Children of both genders participated in this study. Parents/primary caregivers assessed 194 children and 294 children were assessed by their teachers. The results indicated that, for the parents and teachers, the children without problems were more socially skilled. The gender of the children distinguished the repertoire of social skills, according to their parents, mainly the school-age children. For the teachers, considering both school periods, girls were more socially skilled and, for both parents and teachers, boys presented more behavior problems. These data have implications for assessment and intervention procedures.